Neonatal outcomes and congenital malformations in children born after dydrogesterone application in progestin-primed ovarian stimulation protocol for IVF: a retrospective cohort study - Huang J; Xie Q; Lin J; Lu X; Wang N; Gao H; Cai R; Kuang Y (Dove Medical Press, 2019)
Jialyu Huang,* Qin Xie,* Jiaying Lin, Xuefeng Lu, Ningling Wang, Hongyuan Gao, Renfei Cai, Yanping KuangDepartment of Assisted Reproduction, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200011, People’s Republic of China*These authors contributed equally to this workPurpose: Dydrogesterone (DYG) has been demonstrated to be an alternative progestin in the progestin-primed ovarian stimulation (PPOS) protocol with comparable oocyte retrieval and pregnancy outcomes. However, its safety regarding neonatal outcomes and congenital malformations is still unclear.Patients and methods: This retrospective cohort study included 3556 live-born infants after in vitro fertilization and vitrified embryo transfer cycles using the DYG + human menopausal gonadotropin (hMG) protocol (n=1429) or gonadotropin-releasing hormone (GnRH)-agonist short protocol (n=2127) from January 2014 to December 2017. Newborn information was gathered from standardized follow-up questionnaires and/or access to medical records within 7 days after birth. Associations between ovarian stimulation protocols and outcome measures were analyzed by binary logistic regression after adjusting for confounding factors.Results: In both singletons and twins, birth characteristics regarding mode of delivery, newborn gender, gestational age, birthweight, length at birth and Z-scores were comparable between the two protocols. For adverse neonatal outcomes, the two protocols showed no significant differences on the rates of low birthweight, very low birthweight, preterm birth, very preterm birth, small-for-gestational age, large-for-gestational age and early neonatal death after adjustment. Furthermore, the incidence of major congenital malformations in the DYG + hMG protocol (1.12%) was similar to that in the GnRH-agonist short protocol (1.08%), with the adjusted odds ratio of 0.98 (95% confidence interval [CI]: 0.40–2.39) and 0.90 (95% CI: 0.33–2.41) in singletons and twins, respectively.Conclusion: Our data suggested that compared with the conventional GnRH-agonist short protocol, application of DYG in the PPOS protocol was a safe option for the newborn population without compromising neonatal outcomes or increasing congenital malformation risks.Keywords: neonatal outcomes, congenital malformations, dydrogesterone, progestin-primed ovarian stimulation, in vitro fertilization